Ecology : theories and applications - Stiling, Peter. D. (New Jersey : Prentice hall, 1996)
Top selling introductory ecology text covering evolutionary, behavioral, population, community and applied ecology. In this new edition the applied ecology has been completely integrated into the theories of ecology. Introductory biology prerequisite.
Includes Index.
Keywords: Ecology